Constraints on power law cosmology from cosmic chronometer, standard ruler, and standard candle data. Issue 8 (23rd August 2021) - Ryan, Joseph
Abstract: In this paper I investigate how well simple power law expansion fits observational data in comparison to the standard ΛCDM model. I analyze a data set consisting of cosmic chronometer, standard ruler, and standard candle measurements, finding that the ΛCDM model provides a better fit to most combinations of these data than the power law ansatz.